Behavior of banana cultivars exposed to infestation by M. incognita and M. javanica - Zem, Antonio Carlos; Lordello, Luiz Gonzaga E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1981)
Twenty banana cultivars (Musa spp.) were exposed in natural conditions to infestation by two root knot nematodes, namely Meloidogyne incognita and M. javanica. It was found that all cultivars were attacked by M. incognita and eight by M. javanica. However, in an uniform infestation by the Javanese nematode, all cultivars would be eventually attacked by this species. Symptoms shown by the radicular systems are described. Bruning of "seedling" root and cleaning the soil adhering to them, and planting them in soils not infested with Meloidogyne spp. are recommended.